Brain alterations within the first 100 days of HIV infection. (18th December 2014) - Ragin, Ann B.; Wu, Ying; Gao, Yi; Keating, Sheila; Du, Hongyan; Sammet, Christina; Kettering, Casey S.; Epstein, Leon G.
Abstract Objective Brain involvement is a serious complication of HIV infection. The earliest changes in the brain, which represents an anatomic site for viral persistence, are largely unknown. Methods This investigation used quantitative Magnetic Resonance methodologies, including high resolution and diffusion tensor (DTI) imaging, to evaluate the brain in 15 HIV and 20 seronegative subjects. All HIV subjects were antibody nonreactive with assay‐estimated infection duration of less than 100 days. Results Brain volumetric analysis revealed reduced parenchyma with enlargement of the third ventricle and brainstem. DTI quantified loss of white matter integrity in the corpus callosum and diffusion alterations in caudate. Cognitive differences were indicated in psychomotor speed and visual recall. There were no differences between antiretroviral‐initiated and naïve HIV subgroups. Interpretation These findings, quantified within 100 days of infection, shed light on the earliest brain changes in HIV infection. Onset of neural injury may date to initial viral invasion and the transient early period of unchecked viremia and marked immunosuppression of the seroconversion period.